3. CORRELATION BETWEEN THE ZUNG SELF-RATING AND HAMILTON ANXIETY SCALES IN STUDENTS WITH ANXIETY DISORDERS AT THE UNIVERSITY OF MEDICINE AND PHARMACY AT HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the correlation between the Zung Self-Rating Anxiety Scale (SAS) and the Hamilton Anxiety Rating Scale (HAM-A) in students with anxiety disorders at University of Medicine and Pharmacy at Ho Chi Minh (UMP). Subjects and Methods: This cross-sectional descriptive study was conducted on 60 medical students from the UMP, who exhibited symptoms of anxiety disorders, from November 2024 to December 2024. Spearman’s correlation test was used to evaluate the correlation between the two scales: SAS and HAM-A. Results: Based on Spearman’s correlation analysis, the SAS and HAM-A scales in the study group showed a strong correlation, with r = 0.8190 (p < 0.001). Conclusion: The HAM-A scale provides an anxiety assessment result that corresponds well with the SAS scale. Therefore, both scales can be flexibly applied in research and clinical practice. Furthermore, using both scales together not only enhances the reliability of the assessment results but also helps minimize errors due to the limitations of each scale.
Keywords: correlation; SAS; HAM-A; anxiety.